Regional Summer Schools: Widening Learning Opportunities Through Intensive Courses - Ellis, Bronwyn; Sawyer, Janet (Australian and International Journal of Rural Education, 2009)
While many universities now include summer school and other intensive courses as part of their annual programme offerings, undergraduate summer school courses were initiated in one South Australian university by its regional campus. Originally designed to give students who had failed a course the opportunity to catch up, they also enabled students to fast-track their degree, or lighten the workload for a subsequent study period, and provided these students with a distinctive learning experience. Despite much informal favourable feedback from both local students and metropolitan students who have availed themselves of this opportunity, there had not been a formal evaluation of the effectiveness of these regional summer schools, in comparison with the usual delivery modes, prior to the study described in this paper. The positives of the regional campus summer school are demonstrated in these results.